2015
DOI: 10.1088/0143-0807/36/4/045020
|View full text |Cite
|
Sign up to set email alerts
|

Rotational kinematics of a rigid body about a fixed axis: development and analysis of an inventory

Abstract: We present the development, administration, and analysis of a focused inventory on the rotational kinematics of a rigid body around a fixed axis. The inventory, which is made up of 13 multiple-choice questions, was developed on the basis of interactions with students and teachers. The systematic and iterative aspects of the construction of the inventory are illustrated. The questions, which were validated, were administered to a set of teachers (N = 25) and two groups of preuniversity students (N = 74 and 905)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 23 publications
(58 reference statements)
0
37
0
Order By: Relevance
“…It is important to tackle these difficulties, especially during the course of pre-service physics teacher education. Seattha, Yuenyong, and Art-in (2015) and Mashood and Singh (2015) suggest the need for innovative teaching and learning approaches. In the context of a developing country such as Zambia, the need for innovation takes more prominence, given the unavailability of apparatus and equipment for standard experiments.…”
Section: Problem Statementmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to tackle these difficulties, especially during the course of pre-service physics teacher education. Seattha, Yuenyong, and Art-in (2015) and Mashood and Singh (2015) suggest the need for innovative teaching and learning approaches. In the context of a developing country such as Zambia, the need for innovation takes more prominence, given the unavailability of apparatus and equipment for standard experiments.…”
Section: Problem Statementmentioning
confidence: 99%
“…They experienced problems too with centripetal acceleration . Mashood and Singh (2015) suggested this could be a result of lack of differentiation of related but distinct concepts and equations. Rebello and Rebello (2013) found that students considered angular velocity as being distinct for each particle in a rotating body.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of these instructional approaches were also investigated with regard to gender. Among the physics topics, rotational motion was selected for the investigation since rotational motion is a difficult and conceptually rich topic that needs further attention from the physics education research community (Mashood & Singh, 2015). According to a study conducted by Duman, Demirci, and Şekercioğlu (2015), students have difficulties and misconceptions about the fundamental concepts of rotational motion, such as rolling, moment of inertia, rotational energy and torque concepts.…”
Section: / 13mentioning
confidence: 99%
“…According to a study conducted by Duman, Demirci, and Şekercioğlu (2015), students have difficulties and misconceptions about the fundamental concepts of rotational motion, such as rolling, moment of inertia, rotational energy and torque concepts. In addition to these, physics education research on concepts related to rotational motion is limited (Mashood & Singh, 2015). Therefore, in this study attempts were made to test the following null hypotheses as the research is purely quantitative:…”
Section: / 13mentioning
confidence: 99%